Synopsis of Onagraceae (Myrtales) in the state of Santa Catarina, southern Brazil - David Moura Farias; Luís Adriano Funez; André Luís de Gasper (Rodriguésia)
Abstract Onagraceae is a cosmopolitan family with 22 genera and about 660 species, most frequently found in subtropical and temperate regions. In Brazil, 64 species occur across four genera: Epilobium, Fuchsia, Ludwigia, and Oenothera. The family has been widely studied in terms of its anatomy, reproductive biology, taxonomy, and phylogeny; however, studies on Onagraceae in Santa Catarina are scarce, with no complete taxonomic review. Our objective was to review the Onagraceae family and to develop a synopsis of the species that occur in Santa Catarina. A bibliographic review was conducted, along with the analysis of exsiccates from the family collected in the state and deposited in the southern Brazilian herbaria CRI, FLOR, FURB, HBR, JOI, LUSC, and MBM. We identified 31 species, provided identification keys for the genera and species, and commented on each species.